Stay Loyal or Exit the Party? How Openness to Experience and Extroversion Explain Vote Switching. Issue 3 (4th May 2015) - Bakker, Bert N.; Klemmensen, Robert; Nørgaard, Asbjørn Sonne; Schumacher, Gijs
Abstract : Following Hirschman, voters who are discontent with the party they voted for have two options: exit the party and vote for another or stay loyal. The inclination to exit or stay loyal is rooted in the Five Factor Model (FFM) of personality. We test our argument in two panel studies in Denmark and the United Kingdom. We find that citizens open to experience are more likely to switch parties since they are more likely to think about alternatives and take risks. Extroverts identify and commit themselves to organizations and stay loyal in Denmark, but we do not confirm this pattern in the United Kingdom. Our findings demonstrate that electoral volatility is, at least partly, rooted in personality.